Noble Gases in Medicine: Current Status and Future Prospects - David A. Winkler (Oxygen, 2024)
Noble gases are a valuable but overlooked source of effective and safe therapeutics. Being monoatomic and chemically inert, they nonetheless have a surprisingly wide range of biochemical and medically valuable properties. This mini review briefly summarizes these properties for the most widely used noble gases and focuses and research gaps and missed opportunities for wider use of these intriguing ‘atomic’ drugs. The main research gaps and opportunities lie firstly in the application of advanced computational modelling methods for noble gases and recent developments in accurate predictions of protein structures from sequence (AlphaFold), and secondly in the use of very efficient and selective drug delivery technologies to improve the solubility, efficacy, and delivery of noble gases to key targets, especially for the lighter, poorly soluble gases.